2009
DOI: 10.1038/eye.2009.163
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with optic disc haemorrhage in patients with normal tension glaucoma

Abstract: Purpose To evaluate the risk factors associated with optic disc haemorrhage in patients with normal tension glaucoma (NTG). Patients and methods Two hundred and eighty-one eyes of 281 patients with NTG (113 eyes with optic disc haemorrhage and 168 eyes without haemorrhage) were included in this study. Associations between optic disc haemorrhage and various patient-related variables (diabetes; hypertension; hypotension; cardiac disease; stroke; cold hand; migraine; constipation; use of steroids, aspirin, antico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 32 publications
8
39
3
Order By: Relevance
“…45,46 In prospective studies, 42,47 DH has been confirmed as an important prognostic factor for further disease progression, especially in NTG. 42,[48][49][50] In the present study, DH showed no correlation with VFD progression in any of the subfields. One possible explanation for this is that only subjects who could be followed up under topical medication for Z5 years were included in the study population, and eyes with evident progression of VF, where DH is more likely to be encountered, were excluded.…”
Section: Discussioncontrasting
confidence: 68%
“…45,46 In prospective studies, 42,47 DH has been confirmed as an important prognostic factor for further disease progression, especially in NTG. 42,[48][49][50] In the present study, DH showed no correlation with VFD progression in any of the subfields. One possible explanation for this is that only subjects who could be followed up under topical medication for Z5 years were included in the study population, and eyes with evident progression of VF, where DH is more likely to be encountered, were excluded.…”
Section: Discussioncontrasting
confidence: 68%
“…One study showed that use of aspirin and systemic hypertension were associated with DH in eyes with normaltension glaucoma. 23 In our study, the use of aspirin was significantly different between the nonrecurrent and recurrent DH groups. This difference was more pronounced between the recurrent DH group at the same location (21.4%) and different locations (50.0%), occurring at a higher rate in the latter.…”
Section: Discussionmentioning
confidence: 69%
“…Patients in whose eyes DH has never been observed were included in the control group. We compared sex, age, diagnosis, associated systemic abnormalities (diabetes mellitus, systemic hypertension, migraine, tendency to cold hands) obtained through history taking 22 between the DH group and the control group.…”
Section: Methodsmentioning
confidence: 99%